Assessing Risk and Knowledge of Women on Breast Cancer and Providing Lifestyle Advice for the Management of Breast Cancer Risk: Life Sciences-Pharmacy practice for good health promotion - Ishrar Shaik Mohammad Ghouse; Neeluri Prasanth; GaddiGeetha Reddy; Madamanchi Ganga Manasa (International Journal of Life Science and Pharma Research, 2022)
Breast cancer is the most common cancer and is the main cause of cancer mortality among women in the world. Overall, 1 in 28 women is likely to develop breast cancer during her lifetime. Although the mortality rate is decreasing, the incidence is persistently increasing due to urbanization and lifestyle changes. So, there is a need to assess the personal breast cancer risk and increase the knowledge of women on early detection. The present study aims to assess the risk and knowledge of women on breast cancer. The main objective of the study is to identify the women at high risk, to create awareness among women about early screening and detection and to educate lifestyle management to decrease breast cancer risk. A descriptive cross-sectional study was performed during the period of June 2019 to November 2019 in the women attended for mammographic examination. A total of 270 women responded to the study. The results showed that five-year risk is found to be high for 31.1% of women and low for 68.8% of women with a mean of 1.4 and the standard deviation is 1.24. About 14.81% of women were found to have strong lifetime risk and 30.37% of women had average lifetime risk and 54.81% women had usual lifetime risk. The mean lifetime risk of the women is 16.09 and the standard deviation is 10.2. The majority of the participants have low knowledge on breast cancer; BSE, and mammography i.e., 80% of them were lack of knowledge. The mean knowledge score is 6.34 and the standard deviation is 5.45. The women who had high five-year and strong lifetime risk are eligible for breast cancer prevention and management approaches. The women with moderate lifetime risk were advised with regular screening and Breast Self-Examination practices.